KEBIJAKAN MAKRO EKONOMI PADA SISTEM PEREKONOMIAN GLOBAL - Fawza Rahmat (Saqifah: Jurnal Hukum Ekonomi Syariah, 2022)
Discussions on the exchange rate system are often trapped in generalizations without looking at the exact economic conditions of the country concerned. There are five prepositions expressed in the exchange rate system, namely: (1) a country seeks to increase the flexibility of its currency exchange rate; (2) all countries prepare institutions that support a fixed exchange rate system (such as Argentina and Hong Kong) that adhere to the currency board system; (3) the exchange rate system of a country by moving to one of the exchange rate system groups, namely free floating or fixed, while the choice of a system between the two (intermediate regime) such as the target zone is increasingly difficult to maintain; (4) prediction that the world will be divided into several strong currency blocks such as countries using the Euro and American countries using the United States dollar. (5) The fifth preposition emphasizes the importance of creating stability in the exchange rates of the three major world currencies, namely the US dollar, the Euro and the Yen. The macroeconomic discussion talks more about the expansion of global economic development by taking into account all the lines outlined in strategic policies.